2008
DOI: 10.1093/toxsci/kfn142
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Activation of Peroxisome Proliferator–Activated Receptor β/δ (PPARβ/δ) Attenuates Carbon Tetrachloride Hepatotoxicity by Downregulating Proinflammatory Gene Expression

Abstract: Peroxisome proliferator-activated receptor (PPAR) beta/delta-null mice exhibit exacerbated hepatotoxicity in response to administration of carbon tetrachloride (CCl(4)). To determine whether ligand activation of the receptor protects against chemical toxicity in the liver, wild-type and PPARbeta/delta-null mice were administered CCl(4) with or without coadministration of the highly specific PPARbeta/delta ligand GW0742. Biomarkers of liver toxicity, including serum alanine aminotransferase (ALT) and hepatic tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 97 publications
5
44
0
1
Order By: Relevance
“…It was shown that the PPAR␤/␦ agonist GW501516 reduced histopathological changes in the MCD model of steatohepatitis and reduced expression of inflammatory cytokines and chemokines (32). Also, recent data suggest that PPAR␤/␦ protects against liver toxicity induced by environmental chemicals, likely by suppressing proinflammatory genes (42,43). Importantly, Odegaard et al (35) recently showed that PPAR␤/␦ is required for the acquisition of the metabolic and immune phenotypes of alternatively activated macrophages in liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the PPAR␤/␦ agonist GW501516 reduced histopathological changes in the MCD model of steatohepatitis and reduced expression of inflammatory cytokines and chemokines (32). Also, recent data suggest that PPAR␤/␦ protects against liver toxicity induced by environmental chemicals, likely by suppressing proinflammatory genes (42,43). Importantly, Odegaard et al (35) recently showed that PPAR␤/␦ is required for the acquisition of the metabolic and immune phenotypes of alternatively activated macrophages in liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that PPAR␤/␦ may influence the inflammatory properties of Kupffer cells (35). Furthermore, recent data suggest that PPAR␤/␦ is protective against liver toxicity induced by environmental chemicals, possibly by downregulating expression of proinflammatory genes (42,43). Other studies have linked PPAR␤/␦ to proliferation of stellate cells and vitamin A metabolism (16,17).…”
mentioning
confidence: 99%
“…PPAR / is expressed in quiescent HSCs, and especially in activated HSCs in vitro and in vivo but its role is not completely clear yet; indeed PPAR / favors HSCs proliferation but also counterbalances this effect expressing genes involved in esterification of vitamin A (2) and downregulating proinflammatory gene expression, thus working to maintain HSCs in a quiescent phase [69][70][71].…”
Section: Ppar / In Hepatocytesmentioning
confidence: 99%
“…Finally, it has been shown that PPAR / has hepatoprotective effects being able to modulate NF-kB signaling thus attenuating carbon tetrachloride hepatotoxicity [78].…”
mentioning
confidence: 99%
“…3 Additionally, PPARδ agonist may be involved in stem cell and progenitor cell proliferation and protection against apoptosis. [4][5][6] The effects of PPARδ on ES cells are relatively unknown, although a recent study revealed that high glucose-mediated mouse ES cells proliferation levels are required for PPARδ activation. 5 Therefore, PPARδ in ES cells may have an essential role in self-renewal.…”
Section: Introductionmentioning
confidence: 99%